Large-Range, Highly-Sensitive, and Fast-Responsive Optical Fiber Temperature Sensor Based on the Sealed Ethanol in Liquid State Up to its Supercritical Temperature - Yingying Liao; Yi Liu; Yan Li; Changpeng Lang; Kunjian Cao; Shiliang Qu (IEEE Photonics Journal)
A highly-sensitive and fast-responsive optical fiber temperature sensor based on the sealed liquid ethanol with a large detection range was proposed. The ethanol was injected into the fiber Fabry-Perot (FP) micro-cavity through the thin core silica capillary tube (SCT), which was then spliced to a section of singe mode fiber. A section of air core was formed in the thin core SCT near the splicing position. If the volume of the sealed ethanol is much larger than that of the air core, the ethanol can remain liquid state until its supercritical temperature (about 243 °C) at which the ethanol becomes supercritical state. The temperature sensitivity of proposed sensor with a volume ratio 2.89 of ethanol to air reaches –497.6 pm/ °C with an upper detection limit of 220 °C. Meanwhile, the order of the interference fringe can be distinguished by monitoring the transmission loss of the sensor, which can assist wavelength demodulation in the large detection range. Besides, the proposed fiber temperature sensor is with the advantages of fast response (less than 1 s for the temperature variation of about 90 °C) and good repeatability.